Who is contemporary art for? (Palíndromo, 2025)
Contemporary art is configured as a space for experimentation and paradigm transformation, but it still remains accessible to a restricted audience, especially in the school context. This distance highlights the need to reflect on the limits of mediation and curatorship in expanding access. This article aims to discuss possibilities for the democratization of contemporary artistic production without reducing its conceptual complexity. To this end, a critical analysis of curatorial and educational practices in museum institutions is adopted, considering their potentialities and limitations. The results show institutional strategies that promote the active participation of audiences and broaden the understanding of contemporary art. It is concluded that its democratization requires the reconfiguration of museum proposals, the appreciation of community knowledge, and mediation actions that foster the formation of more diverse and critical audiences.
Keywords: art system; public; systemcontemporary art; art/education